2012
DOI: 10.1105/tpc.112.095695
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Microdomain-Associated Protein, Arabidopsis Flot1, Is Involved in a Clathrin-Independent Endocytic Pathway and Is Required for Seedling Development

Abstract: Endocytosis is essential for the maintenance of protein and lipid compositions in the plasma membrane and for the acquisition of materials from the extracellular space. Clathrin-dependent and -independent endocytic processes are well established in yeast and animals; however, endocytic pathways involved in cargo internalization and intracellular trafficking remain to be fully elucidated for plants. Here, we used transgenic green fluorescent protein-flotillin1 (GFP-Flot1) Arabidopsis thaliana plants in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
200
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 80 publications
13
200
0
2
Order By: Relevance
“…Because DRMs include sphingolipid-and sterol-enriched PM microdomains (Cacas et al, 2012), these results suggest that the decrease in 2-hydroxy sphingolipids by knockdown of Os-FAHs decreased the amount of DRMs, and especially PM microdomains. We also found that rice PIP1s, members of a family of PM microdomain proteins (Hachez et al, 2013), were not present in the DRM fraction of OsFAH1/2-KD, although Os-CHC, which does not localize in PM microdomains (Li et al, 2012), was detected, supporting the idea that PM microdomains would decrease in the DRM fraction of OsFAH1/ 2-KD. In addition, in vivo visualization of PM order using di-4-ANEPPDHQ demonstrated that the heterogeneity of the rice cell PM was lower in OsFAH1/2-KD1 than in the wild type.…”
Section: Importance Of Pm Microdomain Organization By 2-hydroxy Sphinsupporting
confidence: 69%
See 3 more Smart Citations
“…Because DRMs include sphingolipid-and sterol-enriched PM microdomains (Cacas et al, 2012), these results suggest that the decrease in 2-hydroxy sphingolipids by knockdown of Os-FAHs decreased the amount of DRMs, and especially PM microdomains. We also found that rice PIP1s, members of a family of PM microdomain proteins (Hachez et al, 2013), were not present in the DRM fraction of OsFAH1/2-KD, although Os-CHC, which does not localize in PM microdomains (Li et al, 2012), was detected, supporting the idea that PM microdomains would decrease in the DRM fraction of OsFAH1/ 2-KD. In addition, in vivo visualization of PM order using di-4-ANEPPDHQ demonstrated that the heterogeneity of the rice cell PM was lower in OsFAH1/2-KD1 than in the wild type.…”
Section: Importance Of Pm Microdomain Organization By 2-hydroxy Sphinsupporting
confidence: 69%
“…Observation of PM microdomain proteins by immunoelectron microscopy or stimulated emission-depletion microscopy has shown that the diameter of PM microdomains in plant cells is <100 nm (Raffaele et al, 2009;Li et al, 2012;Demir et al, 2013). In this study, PM microdomains themselves were observed as highly ordered puncta by the combination of di-4-ANEPPDHQ and TIRFM and were ;250 nm in diameter.…”
Section: Importance Of Pm Microdomain Organization By 2-hydroxy Sphinmentioning
confidence: 49%
See 2 more Smart Citations
“…Both clathrindependent and -independent internalization mechanisms have been described in plants (23,24). Because clathrin has been shown to function in BRI1 endocytosis (9), we addressed genetically whether clathrin is required for the internalization of PRRs.…”
Section: Resultsmentioning
confidence: 99%